PECULIAR FEATURES OF PTCA IN CORONARY PATIENTS WITH BIFURCATION LESIONS - A. O. Oleynik; P. Y. Dovgalevsky; I. B. Shitikov; I. V. Titkov (Российский кардиологический журнал)
The aim of the study was to analyse the clinical and angiographic results of bifurcational coronary balloon angioplasty and/or stenting depending on procedural variables and treatment method. The study included 56 patients with stable angina presenting bifurcational coronary lesions. The stent was implanted in main vessel in 32 patients. 24 patients were treated without stenting. Side branch angioplasty was performed in 16 stented and in 12 nonstented segments. All stenting procedures were performed using three ways: 1) so called «standard» manner without side branch protection during stenting, 2) elsewhere well described «jailed guidewire» technique and 3) hand9mounted two9balloons system proposed by K. Aroney. In 28 cases of successful bifurcational angioplasty an immediate clinical benefit was achieved. Among patients in whom side branch dilatation attempts have failed, 4 were finally free of symptoms, 6 have still demonstrated objective ischemic signs despite of considerable improvement in terms of angina functional class and 3 patients showed no clinical benefit. Conclusion: intact side branch ostium arising from main branch stenosis becomes compromised in large number of cases. 30% of side branch angioplasty attempts fail, of which the majority fall on stented main branch cases. Among types of bifurcation treatment, Aroney’s method showed the least effectiveness. Incomplete bifurcation reconstruction substantially decrease the clinical benefit in these patients. Key words: bifurcation lesion, coronary angioplasty, coronary stenting.